2013
DOI: 10.1007/s12020-013-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and insulin in pancreatic beta-cells

Abstract: Zinc (Zn2+) is an essential element crucial for growth and development, and also plays a role in cell signaling for cellular processes like cell division and apoptosis. In the mammalian pancreas, Zn2+ is essential for the correct processing, storage, secretion, and action of insulin in beta (β)-cells. Insulin is stored inside secretory vesicles or granules, where two Zn2+ ions coordinate six insulin monomers to form the hexameric-structure on which maturated insulin crystals are based. The total Zn2+ content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
165
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(173 citation statements)
references
References 157 publications
3
165
0
Order By: Relevance
“…In the presence of zinc, concentrated in the maturating vesicles via its transport by the zinc transporter ZnT8 [23] (see below), the dimers aggregate to form a hexamer around two Zn 2+ ions. The hexamerization process reduces insulin solubility and triggers its crystallisation, increasing the storage capacity of the insulin secreting vesicles [24,25]. Concomitantly, pH is decreased in the maturating granules via a proton pump (<pH 6) as insulin hexamers are unstable at neutral pH.…”
Section: Zinc In Insulin Processing and Storagementioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of zinc, concentrated in the maturating vesicles via its transport by the zinc transporter ZnT8 [23] (see below), the dimers aggregate to form a hexamer around two Zn 2+ ions. The hexamerization process reduces insulin solubility and triggers its crystallisation, increasing the storage capacity of the insulin secreting vesicles [24,25]. Concomitantly, pH is decreased in the maturating granules via a proton pump (<pH 6) as insulin hexamers are unstable at neutral pH.…”
Section: Zinc In Insulin Processing and Storagementioning
confidence: 99%
“…When insulin is secreted into the extracellular medium during exocytosis, hexamers are rapidly converted into active monomers as the pH increases. This process thus also liberates significant concentrations of Zn 2+ into the circulation, potentially with actions independent to those of insulin [25,26]. 4 …”
Section: Zinc In Insulin Processing and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Six insulin monomers require two Zn ++ ions to form the hexameric-structure on which maturated insulin crystals are based. 12 Some previous studies indicated that the lower serum zinc in diabetics may be due to diabetes related hyperzincuria and impaired gastrointestinal absorption of zinc. 13 In addition to the findings that zinc levels are often low in diabetic, it is also felt that zinc (along with other micronutrients) may participate as an integral component of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Zn is essential for the processing, storage, secretion, and action of insulin in beta (β)-cells where six insulin molecules coordinate with two Zn ions to produce a hexameric-structure based molecule for insulin crystals [20].…”
Section: Discussionmentioning
confidence: 99%